Effect of Recombinant Human Epidermal Growth Factor Impregnated Chitosan Film on Hemostasis and Healing of Blood Vessels - Lee, Sangshin; Jung, Inwook; Yu, Seongcheol; Hong, Joon Pio (Archives of Plastic Surgery, 2014)
Background Bleeding can be a problem in wound debridement. In search for an effective hemostatic agent, we experimented with a chitosan film combined with the recombinant human epidermal growth factor (rh-EGF), hypothesizing that it would achieve effective hemostasis and simultaneously enhance arterial healing.Methods Forty-eight Sprague-Dawley rats were used, and 96 puncture wounds were made. The wounds were divided into the following four groups: treated with sterile gauze, treated with gelatin sponge, treated with chitosan, and treated with chitosan combined with rh-EGF. Immediate hemostasis was evaluated, and arterial healing was observed histologically.Results Groups B, C, and D showed a significant rate of immediate hemostasis as compared to group A (P<0.05), but there were no significant differences among groups B, C, and D. Histologically, only group D showed good continuity of the vessel wall after 1 week. It was the only group to show smooth muscle cell nuclei of the vessel wall.Conclusions We observed that chitosan has an effective hemostatic potential and the mix of rh-EGF and chitosan does not interfere with chitosan's hemostatic capabilities. We also identified enhanced healing of vessel walls when rh-EGF was added to chitosan. Further research based on these positive findings is needed to evaluate the potential use of this combination on difficult wounds like chronic diabetic ulcerations.
Keywords: Epidermal growth factor; Chitosan; Hemostasis